Introduction to webometrics quantitative web research for the social sciences - Thelwall, Michael Arijan (San Rafael, Calif. (1537 Fourth Street, San Rafael, CA 94901 USA) : Morgan & Claypool Publishers, 2009)
Webometrics is concerned with measuring aspects of the web: web sites, web pages, parts of web pages, words in web pages, hyperlinks, web search engine results. The importance of the web itself as a communication medium and for hosting an increasingly wide array of documents, from journal articles to holiday brochures, needs no introduction. Given this huge and easily accessible source of information, there are limitless possibilities for measuring or counting on a huge scale (e.g., the number of web sites, the number of web pages, the number of blogs) or on a smaller scale (e.g., the number of web sites in Ireland, the number of web pages in the CNN web site, the number of blogs mentioning Barack Obama before the 2008 presidential campaign). This book argues that it can be useful for social scientists to measure aspects of the web and explains how this can be achieved on both a small and large scale. The book is intended for social scientists with research topics that are wholly or partly online (e.g., social networks, news, political communication) and social scientists with offline research topics with an online reflection, even if this is not a core component (e.g., diaspora communities, consumer culture, linguistic change). The book is also intended for library and information science students in the belief that the knowledge and techniques described will be useful for them to guide and aid other social scientists in their research. In addition, the techniques and issues are all directly relevant to library and information science research problems.
Introduction -- New problems: web-based phenomena -- Old problems: offline phenomena reflected online -- History and definition -- Book overview -- Web impact assessment -- Web impact assessment via web mentions -- Bespoke web citation indexes -- Content analysis -- Category choices -- Sampling methods -- Example -- Validity -- URL analysis of the spread of results -- Web impact reports -- Web citation analysis, an information science application -- Advanced web impact studies -- Summary -- Link analysis -- Background: link counts as a type of information -- Types of webometric link analysis -- Link impact assessments -- Interpreting the results -- Alternative link counting methods -- Case study: links to ZigZagMag.com -- Content analysis of links -- Link relationship mapping -- Case studies -- Colink relationship mapping -- Link impact reports -- Large-scale link analysis with multiple site groups -- Link differences between sectors, an information science application -- Summary -- Blog searching -- Blog search engines -- Date-specific searches -- Trend detection -- Checking trend detection results -- Limitations of blog data -- Advanced blog analysis techniques -- Summary -- Automatic search engine searches: LexiURL searcher -- Introduction to LexiURL searcher -- LexiURL searcher web impact reports -- Web impact reports, classic interface example -- LexiURL searcher link impact reports -- Link impact reports, classic interface example -- LexiURL searcher for network diagrams -- Rearranging, saving, and printing network diagrams -- Network diagram, classic interface example -- Colink network diagrams -- LexiURL searcher additional features -- Web crawling: SocSciBot -- Web crawlers -- Overview of SocSciBot -- Network diagrams of sets of web sites with SocSciBot -- Other uses for web crawls -- Search engines and data reliability -- Search engine architecture -- Duplicate and near-duplicate elimination -- Comparing different search engines -- Research into search engine results -- Modeling the web's link structure -- Tracking user actions online -- Single-site web analytics and log file analysis -- Multiple-site web analytics -- Search engine log file analysis -- Advanced techniques -- Query splitting -- Virtual memetics -- Web issue analysis -- Data mining social network sites -- Social network analysis and small worlds -- Folksonomy tagging -- API programming and mashups -- Summary and future directions -- Glossary -- References.
Part of: Synthesis digital library of engineering and computer science.
Title from PDF t.p. (viewed on May 8, 2009).
Series from website.
Includes bibliographical references (p. 107-114).
Keywords: World Wide Web -- Statistical methods; World Wide Web -- Research; Social sciences -- Research; Information science -- Statistical methods; Quantitative research; Bibliometrics